Predicting the risk of hospital readmissions using a machine learning approach: a case study on patients undergoing skin procedures - Adhiya, Jigar; Barghi, Behrad; Azadeh-Fard, Nasibeh (Frontiers in Artificial Intelligence, 2024)
Even with modern advancements in medical care, one of the persistent challenges hospitals face is the frequent readmission of patients. These recurrent admissions not only escalate the healthcare expenses but also amplify the mental and emotional strain on the patients. This research delved into two primary areas: Unraveling the pivotal factors causing the readmissions, specifically targeting patients who underwent dermatological treatments. Determining the optimal machine learning algorithms that can foresee potential readmissions with higher accuracy. Amongst the multitude of algorithms tested, including logistic regression (LR), support vector machine (SVM), random forest (RF), Naïve Bayesian (NB), artificial neural network (ANN), xgboost (XG), and knearest neighbor (KNN), it was noted that two models -XG and RF -stood out in their prediction prowess. A closer inspection of the data brought to light certain patterns. For instance, male patients and those between the ages of 21 to 40 had a propensity to be readmitted more frequently. Moreover, the months of March and April witnessed a spike in these readmissions, with about 6% of the patients returning within just a month after their first admission. Upon further analysis, specific determinants like the patient's age, and the specific hospital where they were treated emerged as key indicators influencing the likelihood of their readmission.